Diversidade, dinâmica populacional e uso de recursos aromáticos por abelhas Euglossini em formações florestais do bioma Cerrado - Tosta, Thiago Henrique Azevedo (2018)
Euglossine bees have a Neotropical distribution and great diversity in humid tropical forests. Males of this tribe forage for nectar and aromatic fragrances in diverse sources, being able to be floral or not. Recent studies in the Cerrado show that forest environments contribute to the great diversity of these bees in the Biome, although population estimates indicate the possible occurrence of small populations. The aim of the present study was (i) to verify possible spatial and temporal variations in the alpha and beta diversities of Euglossine bees in Cerrado forest remnants; (ii) to verify the temporal and spatial fluctuations in population sizes, as well as the possible relationship of dependence between the number of marks and recaptures, parameters used in population estimates; and (iii) to verify the effect of color/odor and environmental association on the attraction of males to aromatic baits. With aromatic baits, Euglossine males were sampled in six forest remnants of the Cerrado, in the Triângulo Mineiro region, in two periods 2013-2014 (P1) and 2015-2016 (P2), with a total sampling effort of 280 hours. Only one of the remnants presented a significant difference in alpha diversity obtained in two sampling periods. On the other hand, when the remnants are compared with each other, a greater number of significant differences cases in local diversity was observed. Beta diversity was similar between periods. Temporal and spatial variations were detected in population sizes. The number of recaptured Euglossine males, with the exception of Eulaema nigrita, was shown to be dependent on the number of marked individuals. Estimates allow the detection of natural fluctuations of population sizes and are therefore essential for monitoring studies. There was preference for one type of bait (eucalyptol) and one color (red), but there was no interaction between these two factors. There was an effect of the environment on the choice of the fragrance, but not color. In conclusion, this study revealed that: (i) local and regional diversity appears to be unaffected over time, but may differ significantly when different remnants were compared; (ii) spatial and temporal variations and determination of minimum mark individuals to be achieved for population estimates, which are essential for monitoring studies; and (iii) in addition to the flora of the remnant, the choice of odor and color made by Euglossine males seems to be influenced by the intrinsic relation that each species maintains with its aromatic sources.